PENINGKATAN KEMAMPUAN PENGENALAN GOMETRI MELALUI STRUKTUR RUMAH ADAT MELAYU DI KELOMPOK BERMAIN BINA INSAN - Suriati, Ira; Ali, Muhamad; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe objective want to be achieved in this research is to improve the ability to recognize geometry through the traditional Malay house structure in children aged 3-4 years in Southeast Pontianak Bina Insan Play Group. The method is descriptive with Classroom Action Research consist of planning, implementing, observing, and reflecting. Data collection using observation guidelines, interview guides and documentation. Based on the research and data analysis, concluded that the increase in the ability to recognize geometry could through the structure of Malay traditional house in children aged 3-4 years in the Southeast Pontianak Bina Insan Play Group, can be concluded as follows: (1). Lesson plan to improve the ability to recognize geometry through the traditional Malay house structure is categorized very well; (2). Implementation of learning process to improve ability recognizing geometry through the structure of Malay traditional house considered very well. Means that the implementation of geometry learning has been done based on the learning plan that was made; (3). The results of increasing the ability to recognize geometry through the traditional Malay house structure can be stated well, because every aspect of the ability to recognize the geometry of each children has increased with very high categories. Â Keyword : Geometry, Traditional House